2021
DOI: 10.3762/bjoc.17.2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structures and properties of carbazole-based [6]helicenes fused with an azine ring

Abstract: Novel carbazole-based [6]helicenes fused with an azine ring (pyridine, pyrazine or quinoxaline) have been prepared through a five-step synthetic sequence in good overall yields. Commercially available 2,3-dihaloazines were used as starting materials. To discern the effect of merging an azine moiety within a helical skeleton, the X-ray structures, UV–vis absorption and fluorescence spectra of the helicenes were investigated and compared to that of the parent carbazole-based [6]helicene (7H-phenanthro[3,4-c]carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…28 It can also be assumed that the protonation of the inner helix aza group will destabilize molecules 9a and 9b , destroying the C–H⋯N hydrogen bond and disrupting the planarity of their diazahelicene fragments. Indeed, this study and our previous studies 15–18 have shown that diazahelicenes are essentially planar, in contrast to monoaza analogs. It is also known that benzo[ h ]quinoline (p K a = 10.84 (MeCN) and 4.25 (H 2 O)) is a weaker base by 1.82 p K a units in MeCN and 1.37 units in water compared to isomeric acridine.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…28 It can also be assumed that the protonation of the inner helix aza group will destabilize molecules 9a and 9b , destroying the C–H⋯N hydrogen bond and disrupting the planarity of their diazahelicene fragments. Indeed, this study and our previous studies 15–18 have shown that diazahelicenes are essentially planar, in contrast to monoaza analogs. It is also known that benzo[ h ]quinoline (p K a = 10.84 (MeCN) and 4.25 (H 2 O)) is a weaker base by 1.82 p K a units in MeCN and 1.37 units in water compared to isomeric acridine.…”
Section: Resultssupporting
confidence: 71%
“…Earlier in the process of preparing other helicenes, we found that it is less effective. 17,18 However, in the case of 2,3-dibromopyridine it was the only way for us to obtain double aza[4]helicenes. 16 Therefore, pyridine analogs of compounds 2a and b, e.g.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The same methodology has been applied for the synthesis of azine-fused [4]-, [53,54] [5]- [55] and [6]helicenes [56] 16-21, including double S-shaped [4]helicenes 18 [54] and 19 [57] (Scheme 3). The starting ortho-alkynylated heterobiaryls 12 were synthesized from commercially available 2,3-dihaloazines 11 through subsequent Sonogashira reaction and Suzuki arylation or vice versa.…”
Section: Electrophile-induced Cyclizations Of Ortho-alkynylated Biarylsmentioning
confidence: 99%
“…In the present work, we have designed three azahelicenes: two in which pyrazine and quinoxaline units are laterally fused with the central unit of 9Ha (the resultant systems are denoted as 9HaP and 9HaQ , respectively) and a third one with a larger helical length containing 11 rings, polyaza[11]­helicene (denoted as 11Ha ). As mentioned in the previous paragraph, many Qx -based helicenes have been synthesized recently and chiroptical properties have been studied. ,,,, Similarly, many pyrazine-fused helicenes are also reported in the literature. In addition, extension of helical length has also been shown to improve the results in many cases. ,,, Keeping this in mind, our aim is to explore the effects of introduction of above two aromatic acceptor rings and the enlargement of the helical size on the chiroptical properties such as g CD / g CPL and fluorescence rate constants ( K f ). For an electronic transition, these dissymmetry factors are calculated as , where R is the rotatory strength, and D and G are the EDTM and MDTM strengths, respectively, corresponding to absorption (emission).…”
Section: Introductionmentioning
confidence: 99%